In-Hospital Falls at the Department of Otorhinolaryngology - Kimura, Toshiya; Miura, Makoto; Gyo, Kumiko; Yamada, Koichiro; Honda, Keigo; Hayashi, Yasuyuki; Tanigami, Yuki; Nakahira, Mai; Ikeda, Hiroki (International Journal of Practical Otolaryngology, 2018)
A fall accident is an event that is associated with many disadvantages. In our hospital, 5,259 fall cases have been reported over the past 7 years according to our incident reports, and account for 16.5% of all incident reports. We conducted a detailed examination of 120 of these fall cases at the Department of Otolaryngology. Most of all, “before and after excretion” is a common fall-outbreak-motive reason for falls in all departments. In the field of otolaryngology, “use of drugs” and “walking disorder” are frequently encountered reasons for a fall. Calculation of age-specific fall rates revealed two peaks: around 0 years old and after 80 years old. It is suggested that a fall is associated with a reduced ability for maintaining the standing position. A correlation has been reported between the fall rate and the average length of hospitalization. Both the length of hospitalization of 12.3 days and fall rate of 1.97 among the cases seen at the Department of Otolaryngology are lower than all courses that are in other fields, on average. In the patients seen at the Department of Otolaryngology, the fall rate rises significantly as the length of hospitalization increases. In the Department of Otolaryngology, the fall rate of the malignancy group is high (2.91), irrespective of the treatment regimens. Each of the three items—“14 hospitalization days or more,” “65 years old or older,” and “malignancy”—contributes to falls in patients seen at the Department of Otolaryngology, and multivariate analysis revealed a particularly strong contribution of the previous two items. In elderly patients with expected long-term hospitalization, it is necessary to proactively attempt risk reduction; we first make all patients aware of the risk of long-term hospitalization at the first examination, and divide length of stay into multiple times. We review the assessment score after reexamining the “disease severity” and “performance status” as risk factors for falls, and want to realize more efficient measures for preventing falls in the future.
Keywords: incident reports; risk factors for fall; hospitalization days; older age; malignancy